Influence of Capital Adequacy Ratio (CAR) and Operational Expenses to Operating Income (BOPO) towards Return on Assets (ROA) - Andi Silvan (Riviera Publishing, 2024)
The reason for this ponder is to get data within the shape of a more in-depth clarification of the relationship and impact between the CAR and BOPO proportions on ROA and comes about from handled information concerning how much the relationship and impact between the CAR and BOPO proportions on ROA. This research aims to obtain deeper information about the relationship and influence of the Capital Adequacy Ratio (CAR) on Return on Assets (ROA). The strategy utilized in this considers employment the impact strategy. This sort of investigation is graphic confirmation with a quantitative approach. Information collection procedures utilizing auxiliary information. At that point the information examination procedure employments a computer application program, specifically the Factual Item and Benefit Arrangement (SPSS) adaptation 26. The comes about of examination of different straight relapse conditions delivers a condition, to specific Y = 0.002 + 0.004X1 + 0.000X2 + e. It can be concluded that on the off chance that all free factors are zero, the esteem of the subordinate variable is 0.002. The coefficient esteem of the CAR variable (X1) is 0.004 and the coefficient esteem of the BOPO variable (X2) is 0.000.